THE INFLUENCE OF PERFORMANCE ALLOWANCE AND EMPLOYEE DEVELOPMENT TO EMPLOYEE PERFORMANCE IN STATE ASSETS AND SERVICE OFFICE MANADO - Simanjorang, Monica Indrayanti; Tumbuan, Willem J.F. Alfa (Universitas Sam Ratulangi, 2016)
An organization or company’s best asset is human resource or in this case is employee, because employee performance is related to organization or company’s performance. Performance allowance as a employee’s benefits program that is very important in order to realize the goal of the company. The type research is a quantitative research. The purpose of this research is to determine the effect of performance allowance and employee development in KPKNL Manado, simultaneously and partially. The data was taken using questionnaire to 38 respondents which are all of the employees in KPKNL Manado by using saturated sampling method. Research result shows there is a significant effect of performance allowance and employee development on employee performance simultaneously, there is a significant effect of performance allowance on employee performance, partially. And there is no significant effect of employee development on employee performance, partially. The performance allowance greatly affect the quality of employee performance, it is important to KPKNL Manado so I recommend that performance allowance should be raised to support the employee and employee performance will increase. Keywords: performance allowance, employee development, employee performance